MEMS based monolithic Phased array using 3-bit Switched-line Phase Shifter - Karmakr, A.; Roy, B.; Bhattacharjee, A. K. (Advanced Electromagnetics, 2017)
This article details the design of an electronically scanning phased array antenna with proposed fabrication process steps. Structure is based upon RF micro-electromechanical system (MEMS) technology. Capacitive type shunt switches have been implemented here to cater high frequency operation. The architecture, which is deigned at 30 GHz, consists of 3-bit (11.25º, 22.5º and 45º) integrated Switched-line phase shifter and a linearly polarized microstrip patch antenna. Detailed design tricks of the Ka-band phase shifter is outlined here. The whole design is targeted for future monolithic integration. So, the substrate of choice is High Resistive Silicon (ρ > 8kΩ-cm, tan δ =0.01 and ϵr =11.8). The overall circuit occupies an cross-sectional area of 20 × 5 mm2. The simulated results show that the phase shifter can provide nearly 11.25º/22.5º/45º phase shifts and their combinations at the expense of 1dB average insertion loss at 30 GHz for eight combinations. Practical fabrication process flow using surface micromachining is proposed here. Critical dimensions of the phased array structure is governed by the deign rules of the standard CMOS/MEMS foundry.